2017
DOI: 10.1007/s00134-016-4675-y
|View full text |Cite
|
Sign up to set email alerts
|

Fluid administration in severe sepsis and septic shock, patterns and outcomes: an analysis of a large national database

Abstract: The mean amount of fluid administered to patients with severe sepsis and septic shock in the USA during the first ICU day is less than that recommended by the Surviving Sepsis Campaign guidelines. The administration of more than 5 L of fluid during the first ICU day is associated with a significantly increased risk of death and significantly higher hospital costs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
239
1
11

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 280 publications
(255 citation statements)
references
References 36 publications
4
239
1
11
Order By: Relevance
“…Although the results reported by Marik and colleagues [6] seem to align with those of these RCTs and metaanalyses, it must be stated that EGDT is a complex and multi-dimensional intervention that includes fluids, vasopressors, inotropic agents, and red blood cell transfusion, guided by central venous oxygen saturation. Thus, we are left with an ongoing gap in evidence regarding a "safe" upper limit of fluids in sepsis.…”
mentioning
confidence: 73%
See 3 more Smart Citations
“…Although the results reported by Marik and colleagues [6] seem to align with those of these RCTs and metaanalyses, it must be stated that EGDT is a complex and multi-dimensional intervention that includes fluids, vasopressors, inotropic agents, and red blood cell transfusion, guided by central venous oxygen saturation. Thus, we are left with an ongoing gap in evidence regarding a "safe" upper limit of fluids in sepsis.…”
mentioning
confidence: 73%
“…However, we [3] and others [4] have found associations between excess fluid administration and increased mortality due to septic shock, leading us to recommend a cautious approach to fluid resuscitation [5]. The definition of just how much fluid is adequate (or not) for good management of septic patients has been debated for years, and it is not yet clear precisely how much fluid is "excessive", thereby increasing the risk of mortality.In a recent article in Intensive Care Medicine, Marik and colleagues [6] reported the results of their carefully designed cohort study of a large U.S. database (2013 Premier Hospital Discharge database; n = 23,513 patients) in which they examined the relationships of fluid administration with outcomes (hospital mortality) of severe sepsis and septic shock. They also "assessed trends in the difference between actual and expected mortality in the low fluid range (1-5 L day one fluids) and the high fluid range (5-9+ L day one fluids)".…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Not all is done and new data will be incorporated in further editions. For instance, in this edition, it is recommended to give a minimum of 30 mL/kg of crystalloid solutions within the first 3 h. Interestingly, a recent study found [2] that less fluids were administered to patients with severe sepsis and septic shock in the USA during the first ICU day than recommended by the Surviving Sepsis Campaign guidelines, and this was associated with an increased mortality of 2.3% per liter of fluid administered above 5 L. Hjortrup et al [3] randomized 151 adult patients with septic shock in Scandinavia and found that in patients assigned to fluid restriction (fluid boluses only if severe hypoperfusion was detected), fluid volumes at day 5 and during ICU stay were lower than in the standard care group by more than 1 L with no differences in outcome. The trial was a feasibility trial that actually suggested benefit with fluid restriction but was not powered to address patientcentered outcomes.…”
Section: Surviving Sepsis Campaign Controversiesmentioning
confidence: 99%